Comparative Effectiveness of Blood Pressure-lowering Drugs in Patients who have Already Suffered From Stroke: Traditional and Bayesian Network Meta-analysis of Randomized Trials. Issue 15 (April 2016) - Wang, Wei-Ting; You, Li-Kai; Chiang, Chern-En; Sung, Shih-Hsien; Chuang, Shao-Yuan; Cheng, Hao-Min; Chen, Chen-Huan
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Hypertension is the most important risk factor for stroke and stroke recurrence. However, the preferred blood pressure (BP)-lowering drug class for patients who have suffered from a stroke has yet to be determined. To investigate the relative effects of BP-lowering therapies [angiotensin-converting enzyme inhibitor (ACEI), angiotensin receptor blockers (ARB), β blockers, calcium channel blockers (CCBs), diuretics, and combinations of these drugs] in patients with a prior stroke history, we performed a systematic review and meta-analysis using both traditional frequentist and Bayesian random-effects models and meta-regression of randomized controlled trials (RCTs) on the outcomes of recurrent stroke, coronary heart disease (CHD), and any major adverse cardiac and cerebrovascular events (MACCE). Trials were identified from searches of published hypertension guidelines, electronic databases, and previous systematic reviews. Fifteen RCTs composed of 39, 329 participants with previous stroke were identified. Compared with the placebo, only ACEI along with diuretics significantly reduced recurrent stroke events [odds ratio (OR) = 0.54, 95% credibility interval (95% CI) 0.33–0.90]. On the basis of the distribution of posterior probabilities, the treatment ranking consistently identified ACEI along with diuretics as the preferred BP-lowering strategy for the reduction of recurrent stroke and CHD (31% and 35%, respectively). For preventing MACCE, diuretics appeared to be the preferred agent for stroke survivors (34%). Moreover, the meta-regression analysis failed to demonstrate a statistical significance between BP reduction and all outcomes ( P  = 0.1618 for total stroke, 0.4933 for CHD, and 0.2411 for MACCE). Evidence from RCTs supports the use of diuretics-based treatment, especially when combined with ACEI, for the secondary prevention of recurrent stroke and any vascular events in patients who have suffered from stroke.